ANALISIS PENGARUH CUACA TERHADAP PERUBAHAN PEMBEBANAN LISTRIK PADA PT. PLN (PERSERO) RAYON DENPASAR - Adi Purwa Adnyana, I Made; Dyana Arjana, Gede; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2020)
The research aims to determine the effect of air temperature, wind speed and rainfall on changes in electrical loading. The object in this research is PT. PLN (Persero) Rayon Denpasar. Software used Untulk analyze multiple linear regression models using SPSS software. The results of the analysis showed 10.4% of the electrical burden affected by temperature variables. Then on the rainfall Model 3% electric load is affected by the rainfall variables and on the wind speed model of 2.3% The electrical load is affected by the variable wind speed. A simultaneous 15.8% of the electrical load is influenced by variable temperature, rainfall and wind speeds. The remaining 84.2% is influenced by other causes outside the model.